Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Syariah Indonesia Dengan Manajemen Laba Sebagai Variabel Intervening - Anita Putri (AGHNIYA : Jurnal Ekonomi Islam, 2020)
The objective of the research was to find out and to examine the influence of firm size, asset structure, auditor quality, leverage, institutional ownership, voluntary discloser, firm growth, profitability, and earning management on earning quality partially and simultaneously in manufacture companies listed in BEI (Indonesia Stock Exchange) and to find out the influence of firm size, asset structure, auditor quality, leverage, institutional ownership, voluntary discloser, firm growth, and profitability on earning quality through earning management in manufacture companies listed in BEI. The research used causal method ad secondary data. The population was 81 manufacture companies listed in BEI in the period of 2012- 2015.The samples were 81 companies, taken by using census sampling technique. The data were analyzed by using multiple regression analysis and path analysis with an SPSS software program. The result of the research showed that, simultaneously, independent variables of firm size, asset structure, auditor quality, leverage, institutional ownership, voluntary discloser, firm growth, profitability, and earning management had significant influence on earning quality in manufacture companies listed in BEI in the period of 2012-2015. Partially, independent variables of asset structure, audit quality, profit management, leverage, and profitability had significant influence on profit quality, while the variables of firm size, institutional ownership, voluntary disclosure, and firm growth did not have any influence on earning quality. Earning management could be intervening variable on the correlation of audit quality with earning quality and of firm growth with earning quality. Earning management could not become intervening variable on the correlation of firm size with earning quality, of asset structure with earning quality, of voluntary disclosure with earning quality, and of profitability with earning quality in manufacture companies listed in BEI in the period of 2012-2015.